2020
DOI: 10.18060/23667
|View full text |Cite
|
Sign up to set email alerts
|

Helping Community Partners Build Capacity within Integrated Behavioral Health

Abstract: Social workers are recent additions to integrated health care teams; therefore, there is emerging literature about the work experiences and training needs of social workers in integrated settings. After receiving a Health Resources Services Administration-Behavioral Health Workforce Education and Training (HRSA-BHWET) integrated behavioral health (IBH) grant, our social work program conducted a survey among our social work field education sites to determine training needs. Results of the needs assessment revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…A large number of social workers already work in integrated healthcare settings (Padykula et al, 2020). However, while integrated care education models have been welldeveloped in fields such as nursing, social work integrated care education models are comparatively younger and less developed (Zerden et al, 2018).…”
Section: Integrated Care Trainingmentioning
confidence: 99%
See 4 more Smart Citations
“…A large number of social workers already work in integrated healthcare settings (Padykula et al, 2020). However, while integrated care education models have been welldeveloped in fields such as nursing, social work integrated care education models are comparatively younger and less developed (Zerden et al, 2018).…”
Section: Integrated Care Trainingmentioning
confidence: 99%
“…Social workers require training in many areas to be competent interprofessional practitioners, such as team-based care, cultural competency, inter-team communication, trauma-informed care, and evidence-based practices for physical health assessments (Horevitz & Manoleas, 2013;Mattison et al, 2017;Padykula et al, 2020). In one study, social workers working in integrated care settings in Canada identified specialized education and training to be vital for improving the social worker's integration into integrated healthcare teams (Ashcroft et al, 2018).…”
Section: Integrated Care Trainingmentioning
confidence: 99%
See 3 more Smart Citations